2012
DOI: 10.3109/10409238.2012.745476
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of protein–protein interactions in type I polyketide synthases

Abstract: Polyketide synthases (PKSs) are responsible for synthesizing a myriad of natural products with agricultural, medicinal relevance. The PKSs consist of multiple functional domains of which each can catalyze a specified chemical reaction leading to the synthesis of polyketides. Biochemical studies showed that protein-substrate and protein-protein interactions play crucial roles in these complex regio-/stereo- selective biochemical processes. Recent developments on X-ray crystallography and protein NMR techniques … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 165 publications
(264 reference statements)
1
33
0
Order By: Relevance
“…Accordingly, it would be quite promising to develop a PKS system for obtaining hydrocarbon products with specific chain lengths, oxidation modifications, and branched-chain structures via rational design of the PKS and TE pair. However, carrying out a proof-of-principle study to demonstrate this may be difficult, for it is quite challenging to implement de novo designs or even to use the megaenzyme Type I PKS, due to the complexity of its intermodular and intramodular protein-protein interactions (Khosla et al, 2007;Xu et al, 2013). Over the past two decades, reprogramming modular Type I PKS has attracted considerable attention, and many ingenious strategies been yielded progress (Cane, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…Accordingly, it would be quite promising to develop a PKS system for obtaining hydrocarbon products with specific chain lengths, oxidation modifications, and branched-chain structures via rational design of the PKS and TE pair. However, carrying out a proof-of-principle study to demonstrate this may be difficult, for it is quite challenging to implement de novo designs or even to use the megaenzyme Type I PKS, due to the complexity of its intermodular and intramodular protein-protein interactions (Khosla et al, 2007;Xu et al, 2013). Over the past two decades, reprogramming modular Type I PKS has attracted considerable attention, and many ingenious strategies been yielded progress (Cane, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…The functions of the KS domains from the PUFA synthase were further reaffirmed by site-directed mutagenesis and overexpression. The cysteines at the predicted active sites of these domains are highly conserved in discrete ketoacylsynthase enzymes and KS domains of fatty acid synthase and polyketide synthase in animals, plants, and microbes (14,32,(34)(35)(36)(37)(38). The thiolate form is believed to serve as an "nucleophilic elbow" necessary for the nucleophilic attack in the transacylation reaction (37).…”
Section: Discussionmentioning
confidence: 99%
“…The general mechanisms of the catalytic domains could be inferred from studies of homologs from FAS and other systems, and the identified active site residues correlate by and large with these expectations 45 . The high-resolution structures are thus most useful for understanding particularities of PKS biosynthesis relative to fatty acid assembly.…”
Section: The Dissection Approach To Studying Functional Domainsmentioning
confidence: 94%